Outcome of skin incision by cautery versus steel scalpel in hernia surgery: a prospective cohort study at a tertiary medical college hospital in South India - V., Ragesh K.; S., Mahendran; Mathad, Siddarth (International Surgery Journal, 2017)
Background: Since a long time, skin incisions have routinely been made with scalpels. Now a days there is a shift in trend from this method to electrosurgical skin incisions. However, fear of bad scars and improper wound healing has prevented its wide spread use. The aim of the study was to compare the Diathermy versus Scalpel skin incision in elective hernia surgeries with regards to post-operative pain, post-operative wound infection rate and wound healing. Methods: A total of 200 patients were taken for this study. 100 patients underwent diathermy incision (group A) who were compared with 100 scalpel incision patients (group B). Variables used in this study were postoperative pain, wound infection and scar. Results: Patients with diathermy skin incision were having less post-operative pain which was assessed by visual analogue scale when compared with scalpel incision since the p value was 0.01 which is significant (<0.05). The postoperative infection rate and scar were comparable in both the groups since the p-value is >0.05 in each which is insignificant. Conclusions: Diathermy incisions are therefore less harmful to the skin. It has got more advantages than scalpel incisions like less postoperative pain.